2018
DOI: 10.3389/fimmu.2018.01329
|View full text |Cite
|
Sign up to set email alerts
|

In Search for Reliable Markers of Glioma-Induced Polarization of Microglia

Abstract: Immune cells accumulating in the microenvironment of malignant tumors are tumor educated and contribute to its growth, progression, and evasion of antitumor immune responses. Glioblastoma (GBM), the common and most malignant primary brain tumor in adults, shows considerable accumulation of resident microglia and peripheral macrophages, and their polarization into tumor-supporting cells. There are controversies regarding a functional phenotype of glioma-associated microglia/macrophages (GAMs) due to a lack of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 36 publications
1
29
0
Order By: Relevance
“…Glioblastoma multiforme is the most common brain tumor in adults that is characterized by a marked heterogeneity at the cellular and molecular level [44]. In GBM, tumor-infiltrating microglia and peripheral macrophages are major immune cell populations within the tumor accounting for up to 30% of tumor mass in human GBMs [45]. In a recent study, we presented the expression of recombined immunoglobulin heavy and light chains in tumor-associated macrophages isolated from various types of tumor tissue [20].…”
Section: Discussionmentioning
confidence: 99%
“…Glioblastoma multiforme is the most common brain tumor in adults that is characterized by a marked heterogeneity at the cellular and molecular level [44]. In GBM, tumor-infiltrating microglia and peripheral macrophages are major immune cell populations within the tumor accounting for up to 30% of tumor mass in human GBMs [45]. In a recent study, we presented the expression of recombined immunoglobulin heavy and light chains in tumor-associated macrophages isolated from various types of tumor tissue [20].…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral macrophages mostly appear in perivascular areas while resident macrophages are usually located in the peritumoral zone. A recent study showed that only a small batch of common genes toward species (rat, mice, human) differentiates GB-induced polarization of resident microglia (Walentynowicz et al, 2018). Although many studies tried to decipher the origin of TAMs in the tumor, no clear answer has yet been obtained.…”
Section: Microglia: the Resident Macrophages Of The Cnsmentioning
confidence: 99%
“…Transcriptomic analyses of CD11b+ cells isolated from human GBMs and rodent experimental gliomas showed a small overlap between their expression profiles [21,27,28]. Moreover, computational comparison of genes significantly changed in GAMs from different experimental models and clinical samples revealed only a small set of common genes [29]. This could be due many reasons: technical differences in cell isolation, a presence of mixed subpopulations of cells with different functions, inadequacy of animal models poorly reflecting human pathology or imprecise categorization of M1/M2 markers.…”
Section: Tumor Microenvironment Of Gbmmentioning
confidence: 99%
“…Although, these collected results are biased by differences in isolation procedure and cell identification criteria, the observed heterogeneity of responses may also result from co-existence of pro-and anti-inflammatory subsets of microglia and macrophages at specific phases of tumor evolution as well as dissimilar roles of microglia and peripherally recruited macrophages, which are yet to be understood [30,31]. Noteworthy, functional analysis on compared transcriptomic datasets from isolated GAMs shows similarities in upregulated cellular signaling pathways across all models [29]. It suggests that regardless of the observed differences, there is still an universal mechanism orchestrating polarization of microglia and macrophages within the tumor microenvironment.…”
Section: Tumor Microenvironment Of Gbmmentioning
confidence: 99%